Distribution of Clean Water as A Public Good from Justice Perspective - Muhammad Aditiya Ayoga; Sumartono Sumartono; Tri Yumarni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Water is a very vital natural resource and is needed to determine the sustainability of the life of all living things on this earth. Along with the increase in human population, clean water is increasingly becoming a scarce resource and there is no substitute. This is the main problem faced related to the availability of clean water. The gap between demand and supply of clean water infrastructure is not easy to fulfill, making it a very heavy burden for the government to overcome. Public goods provided by government agencies using the state revenue and expenditure budget and/or regional revenue and expenditure budgets are intended to support the programs and tasks of the agency. As a product of public goods, it needs to be distributed in a younger way to the public. In relation to the concept of justice, the word justice can be interpreted as follows: The quality to be righteous; honest (honesty) Not taking sides (impartiality); fair representation of the facts. The quality of being right Retribution as revenge (vindictive); reward (reward) or punishment (punishment) according to achievements or mistakes. The research method used is a normative juridical approach, namely legal research that uses secondary legal sources, carried out by emphasizing and adhering to the juridical aspects. This type of research used a descriptive approach. As part of public goods whose availability for all Indonesians is guaranteed by the state, the government needs to intervene in order to avoid open and direct competition for these types of goods. The clean water supply policy must have a long vision that is integrated in water supply and management. The efforts that can be done are to improve the performance of PDAM as a regional company that is responsible for providing clean water services in urban areas and increase the PAMSIMAS program in providing clean water services in rural areas.